Outcome of thulium laser enucleation of prostate surgery in high-risk patients with benign prostatic hyperplasia - Vartak, Ketan P. (Urol Ann, 2019)
BACKGROUND: Benign prostatic hyperplasia (BPH) is one of the most common diseases in aging men and a significant cause of burden worldwide. Here, we report our experience of Thulium LASER enucleation of the prostate (ThuLEP) in high-risk patients with BPH. METHODS: This was a prospective study conducted between July 2011 and June 2016. The study participants were patients with a confirmed diagnosis of BPH, who required surgery, and were clinically eligible for ThuLEP. RESULTS: A total of 109 patients were included in the study. Of the total 109 patients, 82 patients had American Society of Anesthesiologists (ASA) Grade 3 and 27 had ASA Grade 4. The most common comorbidity was ischemic heart diseases (72.5%), followed by hypertension (57.8%) and diabetes mellitus (48.6%). During the procedure, a total of 11 (10.1%) patients had a fall in blood pressure requiring noradrenaline or mephentine and seven (6.4%) patients had early left ventricular failure. Sixteen (14.8%) patients had arrhythmias (benign) and seven (6.4%) patients with arrhythmias required antiarrhythmic drugs. The overall duration of surgery ranged from 55 to 70 min, laser time ranged from 25 to 35 min, hospital stay ranged from 30 to 36 h, and the mean catheter time was around 24 h. Overall, the change in hemoglobin ranged from 0.5 to 0.8 g/dL. CONCLUSION: Results show that ThuLEP could be a better option in high-risk patients with BPH.